VIOLENCE AGAINST RURAL WOMEN IN RIO GRANDE DO SUL, BRAZIL: CHALLENGES FOR PUBLIC POLICIES - Patrícia Krieger Grossi; Márcio Lima Grossi; Geovana Gasparotto; Monique Soares Vieira; Ana Rita Costa Coutinho (European Scientific Journal, ESJ, 2014)
A woman in Brazil suffers violence every 24 seconds, but there are women more vulnerable to violence such as rural women. 55.2% rural women revealed that they had experienced some type of domestic violence and almost 50% of them reported a lack of services for women who have been abused (Bagatini et. al., 2013 p.27). This qualitative research focuses on violence against rural women in Rio Grande do Sul, Brazil and the challenges for public policies to guarantee their rights. The main objectives are: to identify the types of violence suffered by rural women; to describe their help seeking process, and to analyse if the safety network for women are able to meet their demands. The data was collected through interviews with representatives of women´s rural movemen, coordinators of women´s policies and rural women, and submitted to content analysis. The results demonstrate the invisibility of violence against women in rural areas, the lack of recognition of women´s work; the lack of transportation to access the network of services when available. Furthermore, there is a need of actions to challenge the patriarchal culture as well as public policies directed to the promotion of women´s autonomy. We conclude that rural women are more vulnerable to violence due to the lack of information about their rights and the economic dependency of their partners, as well as the more traditional gender roles. Some government initiatives is taking place such as the mobile units that will provide legal, social and psychological services to rural women.